Answer:
The roots of the function are x = -5/3 and 3. Select these.
Step-by-step explanation:
The roots of the function are the solutions to the function. They are also called the x-intercepts or zeros. To find them, factor the function completely and solve using the zero product property.
f(x) = (3x+5)(x2-6x+9)2 becomes f(x) = (3x+5)(x-3)^2
Set each factor equal to 0 and solve for x.
(3x+5)=0
3x = -5
x = -5/3
(x-3)^2 = 0
x - 3=0
x = 3
Answer:
-19-28i
Step-by-step explanation:
Simplify and write the answer in standard form, a+bi.
Answer:
I don't need to prove it, I already believe you
Answer:
11
Step-by-step explanation:
1.80m + 0.6s = 12.00
[substitute the value of m into the equation]
1.80×(3) + 0.6s = 12
5.4 + 0.6s = 12
[make s the subject of the formula]
0.6s = 12 - 5.4
0.6s = 6.6
[divide both sides of the equation by 0.6]
0.6s / 0.6 = 6.6 / 0.6
s = 11
To prove that 11 is correct
[substitute the value of m and s into the equation]
1.80m + 0.6m = 12.00
1.80×(3) + 0.6×(11) = 12.00
5.4 + 6.6 = 12.00
12.00 = 12.00